Growth performance and photochemical efficiency of Magnolia elegans planted in restoration area - Azim, Muhammad Amirul Azimuallah (2019)
Magnolia elegans is a newly introduced species for forest plantation and has been trial-planted at high altitude at Terla B Forest Reserve, Cameron Highlands, as part of the restoration project. The main objective of this study was to determine the effect of environmental stress on the photochemical efficiency and growth performance of M. elegans at the restoration site (located approximately at 1320 m above sea level). The growth and photochemical efficiency parameters, such as height, diameter, chlorophyll content and chlorophyll fluorescence were taken. These data were then analysed by using General Linear Model and analysis of variance (ANOVA). The results showed that the species recorded low mean values in growth performances and chlorophyll content when exposed to low light intensity. On the other hand, the results on photochemical efficiency was not significantly difference between months of measurement. The recorded Fv/Fm value which ranged between 0.79 to 0.84 indicates that all the leaves of the planted species were under stress.